Prospects for the Use of the Herb Chamomile in the Manufacture of Dietary Supplements - Аngelina V. Streljaeva (Journal of Global Pharma Technology, 2020)
Objective: Chamomile flowers is a widely studied pharmaceutical raw material, however, pharmaceutical herb chamomile herbal raw material practically has not been studied, but in practice is an interesting and promising item for further study. The objective of the study was carrying out of the analysis of the herb chamomile raw material (two types-fresh and dried). Method: In accordance with the Russian SP (State Pharmacopoeia) procedures, there were produced etheroleum and alcohol extract. Moisture content was determined as for dried raw material: 14.00±0.74%, for fresh raw material: 71.40±2.23%. Quantitative and qualitative composition was assessed by GLC (gas-liquid chromatography, mass detector) and HPLC (high-performance liquid chromatography) methods. Results: As of comparative analysis of etheroleum and alcoholic extract from herb chamomile, it should be pointed out that azulene derivatives were present in etheroleum and in alcoholic extract; however, chamazulene as such was identified just in etheroleum. In alcoholic extract there was no chamazulene. In alcohol extract there were identified vitamins, flavonoids (kaempferol is the important one), phenol compounds, coumarins, organic acids-ferulic acid and its derivatives, peptides and sugars. Conclusion: The herb chamomile is both a promising dietary food supplement, and a pharmaceutical preparation. There are a lot of studies concerning the determination of herbal`s bioactive components. This process is important for quality control of herbs and its products.Keywords: Herb chamomile, Chamazulene, Matricin, Kaemferol, Ferulic acid.